L−Lysine Amino Acid Adsorption on Zeolite L: a Combined Synchrotron, X‐Ray and Neutron Diffraction Study. Issue 10 (28th September 2020) - Beltrami, Giada; Martucci, Annalisa; Pasti, Luisa; Chenet, Tatiana; Ardit, Matteo; Gigli, Lara; Cescon, Mirco; Suard, Emmanuelle
Abstract: Invited for this month's cover are the groups of Annalisa Martucci and Luisa Pasti at the University of Ferrara (Italy). The cover picture shows L‐lysine amino acid adsorption on zeolite L. The role of zeolite channels in the stabilization of the lysine absorbed and the effect of water on protein structure are elucidated at atomistic level. The stabilization of the L α‐helical conformation is related to strong H‐bonds between the tail aminogroups of lysine molecules and the Brønsted acid site as well as to complex intermolecular H‐bond system between water molecules, zeolite and amino acid. Read the full text of their Full Paper at 10.1002/open.202000183 . Abstract : "… These results can be transferred to investigation of stereochemistry in related microporous materials… Find out more about the story behind the front cover research at 10.1002/open.202000183 .